C‐X‐C chemokine receptor 7. Issue 1 (26th June 2012) - Yates, Travis J.; Knapp, Judith; Gosalbez, Miguel; Lokeshwar, Soum D.; Gomez, Christopher S.; Benitez, Anaid; Ekwenna, Obi O.; Young, Ezekiel E.; Manoharan, Murugesan; Lokeshwar, Vinata B.
Abstract BACKGROUND: C‐X‐C chemokine receptor 4 (CXCR4) and CXCR7 are 7‐transmembrane chemokine receptors of the stroma‐derived factor (SDF‐1). CXCR4, but not CXCR7, has been examined in bladder cancer (BCa). This study examined the functional and clinical significance of CXCR7 in BCa. METHODS: CXCR4 and CXCR7 levels were measured in BCa cell lines, tissues (normal = 25; BCa = 44), and urine specimens (n = 186) by quantitative polymerase chain reaction and/or immunohistochemistry. CXCR7 function in BCa cells were examined by transient transfections using a CXCR7 expression vector or small interfering RNA. RESULTS: In BCa cell lines, CXCR7 messenger RNA levels were 5‐ to 37‐fold higher than those for CXCR4. Transient overexpression of CXCR7 in BCa cell lines promoted growth and chemotactic motility. CXCR7 colocalized and formed a functional complex with epidermal growth factor receptor, phosphoinositide 3‐kinase/Akt, Erk, and src and induced their phosphorylation. CXCR7 also induced up‐regulation of cyclin‐D1 and bcl‐2. Suppression of CXCR7 expression reversed these effects and induced apoptosis. CXCR7 messenger RNA levels and CXCR7 staining scores were significantly (5‐ to 10‐fold) higher in BCa tissues than in normal tissues (P < .001). CXCR7 expression independently associated with metastasis (P = .019) and disease‐specific mortality (P = .03). CXCR7 was highly expressed in endothelial cells in high‐grade BCa tissues when compared to low‐grade BCa and normal bladder. CXCR7 levels were elevated in exfoliated urothelial cells from high‐grade BCa patients (P = .0001; 90% sensitivity; 75% specificity); CXCR4 levels were unaltered. CONCLUSIONS: CXCR7 promotes BCa cell proliferation and motility plausibly through epidermal growth factor receptor receptor and Akt signaling. CXCR7 expression is elevated in BCa tissues and exfoliated cells and is associated with high‐grade and metastasis. Cancer 2013. © 2012 American Cancer Society.